3y+37=-2(y-6)

Simple and best practice solution for 3y+37=-2(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+37=-2(y-6) equation:


Simplifying
3y + 37 = -2(y + -6)

Reorder the terms:
37 + 3y = -2(y + -6)

Reorder the terms:
37 + 3y = -2(-6 + y)
37 + 3y = (-6 * -2 + y * -2)
37 + 3y = (12 + -2y)

Solving
37 + 3y = 12 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
37 + 3y + 2y = 12 + -2y + 2y

Combine like terms: 3y + 2y = 5y
37 + 5y = 12 + -2y + 2y

Combine like terms: -2y + 2y = 0
37 + 5y = 12 + 0
37 + 5y = 12

Add '-37' to each side of the equation.
37 + -37 + 5y = 12 + -37

Combine like terms: 37 + -37 = 0
0 + 5y = 12 + -37
5y = 12 + -37

Combine like terms: 12 + -37 = -25
5y = -25

Divide each side by '5'.
y = -5

Simplifying
y = -5

See similar equations:

| 123=3x^2 | | 6x/2−8x/1=2 | | 5x+7+2=12+3-3x | | 8x-1=9x-2 | | -3y+37=-2(y-6) | | 25p^2-16= | | x/26.75=35.67 | | 3s+10=5s+3 | | y=-6+34 | | 13x+7=16x-4 | | -2(w+8)=-5w-43 | | y=8x-128 | | 26.75*x=35.67 | | b-3/5=-1 | | 4x-8+6x+9= | | 0=16t^2+120t | | 3(3x+4)=21 | | 6(x+9)=3(8+3x) | | 2/3p=10 | | 120=50 | | 3x=-14x | | 7a+84=7 | | 22x+6-24x=5-9 | | 3(y+5)+5y=7 | | -14r-6r-7r+-13=2 | | xsquared=324 | | 8=-4x+8(x-2) | | 3v^2-19v-40=0 | | 111-3x^2=0 | | 8+7x=4x+41 | | 20y-9y-4y+2y-8y=19 | | 2(2x-7)=7 |

Equations solver categories